Sustainability as a transversal dimension in tourism competitiveness: A critical review of the TTDI evolution - Such Devesa, María Jesús (2025)
The new Travel and Tourism Development Index (TTDI) of the World Economic Forum (WEF), an update of the previous Travel and Tourism Competitiveness Index (TTCI), raises expectations. It represents a first step and suggests a greater concern for addressing tourism’s contribution to the sustainable development of countries. This study reviews the main changes introduced in the index’s evolution, which adopts a different methodological approach by incorporating more dimensions, pillars, and variables. It seeks to address some previously existing criticisms and provides an updated measure of destination development and competitiveness. Hence, the inclusion of sustainability as a new dimension in the TTDI reflects this concern, as it has become a crucial issue for destination development in recent years. The main conclusions highlight that, despite efforts to integrate and offer a broader approach to competitiveness with a focus on development, adopting a truly holistic perspective on sustainability across all its measures remains an essential and unresolved challenge.